Synthesis of Hard Carbon from Waste Teak Wood Powder as Anode Material for Lithium-ion Batteries - Alfi Nur Aini; Dewi Ratnasari; Aninda Artatriska Meilana; Hendri Widiyandari (Universitas Sebelas Maret, 2021)
Electrochemical energy storage technologies such as rechargeable batteries show considerable progress due to their high efficiency, flexible power, long life cycle, and low maintenance. Graphite is a common anode material used in lithium-ion batteries. However, there are several shortcomings in graphite anode material, one of which is poor structural stability. Therefore, hard carbon is the most promising candidate for lithium-ion battery anodes due to its high storage capacity, low working potential, and cycle stability. This research utilizes teak sawdust waste as a hard carbon battery anode. They were approached by the carbonization method at temperatures of 350°C and 450°C. In general, X-Ray Diffraction (XRD) results show an amorphous structure of carbon atoms. The morphological structure known through the Scanning Electron Microscopy with Energy Dispersive X-ray (SEM-EDX) test shows a fiber shape. The mass percent of carbon at a temperature of 450°C was higher than at a temperature of 350°C, which was 67.93%. Then the battery performance test was carried out with the highest discharge capacity value obtained at a temperature of 450°C at 191.56 mAh/g. Based on the results of this study, teak sawdust waste material has the potential as an anode for rechargeable batteries and can prevent environmental pollution.